Time Fiction - Biënnale Gelderland 1998. - Biënnale Gelderland 1998; Hessing, Marjolijn; Van Reekum Museum, Apeldoorn; Museum voor Moderne Kunst, Arnhem; Centrum Beeldende Kunst, Nijmegen; Galerie Marzee, Nijmegen (Arnhem : Biënnale Gelderland, 1998)
Arts, Arno ; Bennema, Aafke ; Bossmann, Ernie ; Broek, Kimmy ten ; Dijkman, Bart ; Fekkes, Jurriaan ; Groen, Lucien ; Kaptein, Marcel ; Kroneman, Jaap ; Mahabier, Anand ; Najand, Soheila ; Odijk, Erik ; Oerlemans, Hester ; Overtoom, Marry ; Pollet, Inge ; Rogge, Cornelius ; van Rooijen, André ; Ruegebrink, Nana ; Savert, Anneke ; Slaats, Annelies ; Sommers, Wilma ; Strik, Maria ; van Swaay, Ruth ; Symons, Jerome ; Teulings, Raoul ; vGtO ; Videler, Mariëlle ; Vos, Jan ; Wesselo, Erik
tent. per kunstenaar [2 p.]
Nederlands
Time Fiction : Biënnale Gelderland 1998, Van Reekum Museum, Apeldoorn, Museum voor Moderne Kunst, Arnhem, Centrum Beeldende Kunst, Nijmegen, Galerie Marzee, Nijmegen, Stedelijke Musea, Zutphen
boek
Keywords: Nederland